(untitled) (Research, Society and Development, 2021)
Objective: to carry out comparative evaluation in the short term of physiological parameters and cardiopulmonary variables in newborns admitted to the Neonatal Intensive Care Unit (NICU) who have physical therapy follow-up. Methodology: this is a descriptive, comparative, prospective of quantitative analysis study carried out with 9 newborns under 40 weeks of gestational age, admitted to the NICU, in April 2021. Data were collected from patients’ electronic medical records, interviews with those responsible by newborns and observation of physiological parameters and other cardiopulmonary variables, 5 minutes before and 5 minutes after a single physical therapy intervention. Results: the majority of newborn volunteers were male (66.67%), who were born via cesarean section (88.89%), from young adult mothers. Only 1 of the newborns was using non-invasive ventilatory support, the rest were on spontaneous ventilation. The average gestational age was 256 days, the average height was 44.92 cm and the birth weight was 2.474 g. Prematurity was the most observed disorder among the participants (66.67%), followed by the transient tachypnea of ​​the newborn (44.44%). The physiological parameters showed variations when comparing the moments before and after physical therapy intervention, the heart rate did not show any significant difference (p = 0.15), the respiratory rate obtained a very significant difference (p = 0.008) and peripheral oxygen saturation showed extreme significance (p = 0.0008). Conclusion: physiotherapy in the NICU can contribute to the parameters of neonates such as a reduction in respiratory rate and an increase in peripheral oxygen saturation while heart rate has not undergone any significant change.